ANALISIS LAPORAN ARUS KAS UNTUK MENILAI KINERJA KEUANGAN PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Kaloh, Trisilia; Ilat, Ventje; Pangerapan, Sonny (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
Â A necessity for companies to include cash flow statements in financial statements. One analysis of financial performance using the cash flow statement is the ratio of cash flow statements. The purpose of this study was to find out the financial performance of six food and beverage companies during 2014-2017. This study uses the ratio analysis method. The ratio used in this study is the ratio of operating cash flows, the ratio of operating cash flow to interest, the ratio of capital expenditure, the ratio of total debt, and the ratio of cash flows to net income. From the results of calculations using the ratio analysis of cash flow reports obtained that from the six food and beverage companies namely PT. Tiga Pilar Sejahtera Food Tbk, PT. Delta Djakarta Tbk, PT. Mayora Indah Tbk, PT. Nippon Indosari Corpindo Tbk, PT. UltraJaya Milk Industry & Trading Company Tbk, PT. Indofood Sukses Makmur Tbk has a very good improvement, although not too high. Keywords: Cash flow statement, Operating cash flow, Cash flow ratio, Financial performance, Bursa Efek Indonesia